EXPLORING COMPLEX SENTENCES AND METPHORS IN ONLINE NEWS ARTICLES ABOUT COVID-19 IN ASIA TIMES - Retno Indriyani; Mashadi Said (INFERENCE: Journal of English Language Teaching, 2022)
This research aims to find the use of complex sentences and metaphors in online news article about Covid-19 in Asia Times. This research employs descriptive qualitative approach to examine five online news articles about Covid-19 in Indonesia containing complex sentences and seven news articles about Covid-19 in Indonesia containing metaphors posted in Asia Times. The writer uses the Verspoor’s and Azar’s theories to examine complex sentences and Lakoff and Johnson’s conceptual metaphor theory to examine metaphors. The result shows that in 5 news articles writing the authors used 115 complex sentences and 40 or (34.8%) of which are modified by noun clauses, 36 sentences (31.3%) are modified by adjective clauses, 32 sentences (27.8%) are modified by adverbial clauses, and 7 sentences (6.1%) are modified by multiple subordinate clauses. This implied that teachers should emphasize on the use of noun clauses in complex sentences when teaching writing. Secondly, the result demonstrates that in seven news articles the authors used 95 metaphors categorized into three types of metaphors: 64 or 67.3% are ontological metaphors, 16 or 16.8% are orientational metaphors, and 15 or 15.9% structural metaphors. In addition, this implied that teachers should be aware of the use of metaphors in various reading text genres specifically online articles.